Examining U.S. drivers' characteristics in relation to how frequently they engage in speeding on freeways. (February 2022) - Kim, Woon; But, Joanne; Anorve, Victoria; Kelley-Baker, Tara
Highlights: This study examines differences between non-, occasional, and frequent speeders. Age and engagement in red-light running are the greatest associated determinants. Speeders also engage in distracted, aggressive, unbelted, and drunk driving. Education and aggressive driving behavior interact with speeding behavior. Frequent speeders tend to enjoy driving fast and disagree with speed limits. Abstract: Speeding and speed-related crashes have consistently represented over 25% of all traffic fatalities over the past two decades. The severity of these speed-related incidents not only impact the drivers but all road users. Thus, characterizing drivers who speed, understanding their motivations, and identifying the types of risky driving behaviors associated with speeding play a critical role in developing, implementing, and sustaining effective countermeasures. Using a survey administered to a U.S. nationally representative sample (N = 2, 930 licensed drivers aged 16 or older), this study develops a partial proportional odds model to examine differences in characteristics between types of speeders – frequent, occasional, and non-speeders – and explores characteristics and risk driving behaviors that are most associated with speeding behavior. Additionally, motivations for speeding are examined for drivers who frequently speed compared with those who occasionally speed. Results show speeders tended to engage in other unsafe driving behaviors, such as distracted, aggressive, unbelted, and alcohol-impaired driving. Among demographic and socio-economic variables examined in this study, drivers' age was the greatest associated determinant. The association with engagement in red-light running, however, outweighed that with drivers' age. Interestingly, the interaction between educational attainment and engagement in aggressive driving was also predictive of speeding behavior. For motivations for speeding, frequent speeders were more likely to report enjoying driving fast and disagreeing with speed limits compared with occasional speeders. The findings of this study are useful towards identifying the various characteristics and behaviors of drivers who engage in speeding, which can provide future insights into where effective countermeasures and prevention efforts should be focused.